Influence of antilymphocyte and antipolymorphonuclear sera on the pyrogenic effect of scarlet fever toxin - Hríbalová, V; Castrová, A; Pekárek, J (Folia microbiologica, 1979)
The role played by lymphocytes in the pyretic response to scarlet fever toxin (ET) was studied in vivo using antilymphocyte serum (ALS). Two i.v. injections of ALS inhibited the pyretic response to a subsequent ET injection in rabbits. The course of endotoxin fever remained uninfluenced by ALS. Antipolymorphonuclear serum had no effect on the pyretic response to either of the toxins. Pretreatment with ALS also inhibited the skin reaction after i.d. injection of ET. These findings are further evidence a mediating role of lymphocytes in the biological effects of ET, among other things in the release of endogenous pyrogen.
Keywords: Male; bakteriální toxiny; kožní testy; Leukocytes; Rabbits; Streptococcus pyogenes; Leukocyte Count; Animals; Antilymphocyte Serum; Fever; Neutrophils; antilymfocytární sérum; spála; Endotoxins; neutrofily; horečka; exotoxiny; mužské pohlaví; Female; antisérum; Skin Tests; Pyrogens; počet leukocytů; ženské pohlaví; Exotoxins; zvířata; endotoxiny; Salmonella paratyphi B; pyrogeny; Bacterial Toxins; Scarlet Fever; Immune Sera; králíci; leukocyty